Mupirocin reduces ciliary beat frequency of human nasal epithelial cells - Birk, Richard; Aderhold, Marc Christoph; Schell, Angela; Eschenhagen, Till; Kramer, Benedikt; Hörmann, Karl; Sommer, Ulrich (European archives of oto-rhino-laryngology and head & neck, 2016)
Mupirocin is used worldwide for topical treatment of infected skin lesions, impetigo, and especially for nasal decolonization of patients with carriage of Staphylococci, including methicillin-resistant Staphylococcus aureus. Nevertheless, data regarding the effects of mupirocin on the nasal mucosa, in particular on ciliary beat frequency (CBF), is lacking to date. We tested the CBF of ciliated nasal epithelial cells under the influence of Mupirocin-calcium dissolved in tert-butyl alcohol (TBA) containing media in different concentrations comparable to clinical use. Ringer’s lactate solution and TBA served as negative control. Cells were visualized with a phase contrast microscope, and the CBF was measured with the SAVA system’s region of interest method. Mupirocin-calcium dissolved in TBA led to a statistically significant time- and concentration-dependent decrease in CBF compared to the negative control. TBA addition without mupirocin also led to a significant decrease in CBF, although to a lesser extent than mupirocin/TBA. In conclusion, CBF of human nasal epithelia is significantly reduced by mupirocin-calcium-containing solutions in therapeutic concentrations. Due to our results in this study, mupirocin as a nasal decolonization agent should be used only with care, with a strictly set medical indication, and additional care measures should be considered.
Gesehen am 27.02.2019